2020
DOI: 10.1111/inm.12795
|View full text |Cite
|
Sign up to set email alerts
|

Consumers living with psychosis: Perspectives on sexuality

Abstract: Mental health clinicians work within a recovery framework that is rights based and emphasizes positive and respectful approaches to working with mental health consumers. Mental health nurses’ practice is also predicated on holism and inclusiveness, yet consumers’ sexuality is sometimes neglected and rights in this area overlooked. Also overlooked is sexuality as an area for investigation, particularly from a consumer perspective, even though it constitutes part of consumers’ broader remit of sexual health. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The authors of 13 studies reported on service users’ expectations of the types of interventions delivered by mental health nurses [ 19 , 21 , 25 , 32 , 33 , 50 , 51 , 52 , 54 , 56 , 62 , 63 , 95 ]. Providing psychosocial support and fostering hope were identified as core interventions across multiple studies [ 50 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of 13 studies reported on service users’ expectations of the types of interventions delivered by mental health nurses [ 19 , 21 , 25 , 32 , 33 , 50 , 51 , 52 , 54 , 56 , 62 , 63 , 95 ]. Providing psychosocial support and fostering hope were identified as core interventions across multiple studies [ 50 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Across 13 studies, services users reported notable negative views of mental health nurses, which included skills deficits, negative attitudes, and poor therapeutic engagement [ 20 , 23 , 25 , 32 , 42 , 43 , 44 , 45 , 48 , 55 , 59 , 61 , 62 ]. For example, in a study involving 119 inpatient service users from a single Mental Health service in England, the authors reported that MHNs seemingly lacked the necessary skills [but did not provide examples] to address their needs [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further compounding and widening the sexology-mental health-clinician gap, Quinn et al (11), Evans (12), and Brand et al (13) emphasis the lack of, and barriers to positive sexual experiences for patients with mental illness and show that patients' are reluctant to self-report sexual dysfunction to clinicians. This reluctance is contrary to the anecdotal evidence presented by Baggaley (14) which suggests that sexual dysfunction has a considerable impact on quality of life (15) and adherence to antipsychotic medications (16).…”
Section: Mental Health and Sexual Healthmentioning
confidence: 99%
“…The expression of sexuality can be impacted by various considerations, including psychological, social, cultural, legal and religious influences ( 3 ). Sexuality and sexual functioning are aspects of an individual's sexual health and are essential components of the individual's holistic health ( 4 ), with most people feeling the desire to have an intimate relationship and to engage in sexual activity, including those with mental illness ( 5 ). The World Health Organization ( 2 ) defines sexual health as:…”
Section: Introductionmentioning
confidence: 99%